Konut Projelerinde, Ön Tasarım Aşamasında, Fonksiyonel Elemanlara Dayalı Maliyet Tahmini İçin Bir Model Geliştirilmesi - Erdem, Ali Ercüment (Fen Bilimleri Enstitüsü, 1996)
Günümüz dünyasında kıt olan kaynakların etkin bir şekilde değerlendirilebilmesi, inşaat işletmelerinin yapım işlerine daha az risklerle girebilmelerinin sağlanması, mal sahibinin bütçesini yapım işlemleri başlamazdan önce ayarlayabilmesi için inşaat sürecinin çeşitli safhalarında kullanılmak üzere çeşitli maliyet tahmin modelleri geliştirilmiştir. Bu modellerden bazıları ön tasarım evrelerinde kullanılırken bazıları da tasarım bittikten sonra kullanılırlar. Ön tasarım aşamasında kullanılan modellerin avantajları maliyet tahmininin yanında maliyet planlamasına da olanak vermeleridir. ön tasarım aşamasında kullanılan modellerden biri de fonksiyonel elemanlara dayalı maliyet tahmin modelidir. Diğer maliyet tahmin modellerinin aksine bu model, binayı bir bütün olarak kabul edip binanın birim maliyetinden yola çıkarak tasarlanı İması uygulanması düşünülen binanın toplam maliyetini tahmin etmek yerine, binaları alt sistemlerine (fonksiyonel elemanlara) ayırarak bunların birim maliyetlerinden toplam bina maliyetine ulaşmayı hedeflemiştir. Geliştirilmeye çalışılan modelde bina, kendisini oluşturan fonksiyonel elemanlarına ayrılmış ve bu fonksiyonel elemanların birim inşaat alanı başına düşen miktarlarının analizleri yapılmıştır. Ancak bu analizler yapılırken, ülke düzeyindeki konut stoğunu temsil eden konut projeleri çeşitli kriterlere göre sınıflandırılmış ve her sınıfın ortalama değerleri ayrı ayrı hesaplanarak tahminde başarı yüzdesinin arttırılmasına çalışılmıştır. Daha sonraki aşamada, her fonksiyonel elemanın gövde ve kaplama kısımları ayrılmış ve bunlar için değişik nitelik ve maliyetlerde alternatifler hazırlanmıştır. Aslında tezin çıkış noktası binanın nitelik sınıfını ve toplam inşaat alanını kontrol altında tutarak, kontrollü bir maliyet planlamasına ve maliyet tahminine olanak veren bir model geliştirmekti. Bilindiği gibi TC. Bayındırlık ve iskan Bakanlığı her sene kalite sınıflarına göre birim inşaat maliyetleri cetvelleri yayınlamaktadır. Yayınlanan bu cetvellerde her sınıf için, kullanılan kaplama malzemelrinin niteliklerinin aynı oldukları kabul edilmekte (lüks inşaat, birinci sınıf inşaat vb.) ve ara değerlere ulaşılamamaktadır. Oysa geliştirilen bu modelde her fonksiyonel elemanın nitelik sınıfı ve fiyatı ayrı ayrı belirlenebilmekte bu da binanın toplam maliyetinin etkin bir şekilde kontrol altına alınmasını sağlamaktadır.

Cost planning and estimating models are applied in construction sector in order to provide most efficient use of the limited resources, which is also case for many other sectors. It would be of great importance for the parties of construction i.e. the contractor and client that the cost of the building be estimated as the cost of construction is generally while a high level of competition is encountered in the market as well. The purpose of the client in the estimation of he cost of construction is to learn about the amount to be needed in financing the project, while the purpose of the contractor is to offer the best to be awarded the tender and to establish the amount to be proposed for the job in order to make it a profitable business. Therefore cost estimation becomes an important subject for both parties for different purposes. Considering the purposes given above, cost estimation models have been developed at various fields of the construction sector. Some of those are utilized at the pre-design phase while some others are used at the phase where the design is completed and detailed drawings are made. The models thai are used during the pre-design phase estimate the approximate cost of the building. The estimations are not often accurate. The methods used when the design and detailed drawings are completed are more accurate with regard to their cost estimation. Within the construction period, the aims of the cost estimation models depending on the development of the design phase are different. The aims of the models used during the pre-design stage are to estimate the cost of the building and to compare the estimated cost with the budget reserved for the job. This allows the designer and the client to make a selection from a range of alternative building design and to choose best possible alternative before proceeding to the application plans. xi The cost estimation models that are used in the detailed drawings phase aim to estimate the cost of the building for both the client and the contractor. Though this model has a high level of estimation accuracy, it will be difficult to plan the cost. On the other hand, various models are used to estimate cost by the developments in the computer technology. Cost estimation models are divided into two groups, namely, traditional and improved cost estimation models. These models are subdivided into different headings. 1) Traditional cost estimation models a) Cost estimation models using unit price b) Cost estimation models considering functional models c) Cost estimation models considering construction procedures d) Cost estimation models considering resources 2) Improved cost estimation models a) Causative and experimantal cost estimation models b) Regression cost estimation models c) Simulation cost estimation models Of the traditional cost estimation models, the one considering functional elements is used during the preliminary stages of design. This model aims to estimate the cost of the building by dividing it to sub-systems and compute the total cost by adding up the costs of such. For that purpose, many building audit corporations divided the buildings into functional elements in order to make efficient cost estimations. The BMBS (Building Cost Data System) functional element classification method has been used within this thesis. This system divides the buildings into six sub-systems: XII 1) LOWER SHELL 2) EXTERNAL CLAUSURE a) Windows b) External doors c) External walls 3) UPPER SHELL 4) PARTITIONS a) Internal doors b) Internal walls 5) SLABS AND STAİRS a) Slabs b) Stairs 6) STRUCTURES a) Frame b) Foundations The cost estimation model that is studied in the thesis also considers functional elements. The aim in developing this model is to establish various design alternatives by inspecting the quality and the cost of the building during the pre-design phase. For that purpose, the quantity and quality analyses of the functional elements have been carried out along the thesis. Within the first stage, 30 housing projects were examined in order to make functional element analysis. During the exeminations, some project specification were found to have influance on the number of functional elements. These might shortly be given under the following headings: a) The planning chart b) The number of housing units on a floor c) Coverage of the floors d) Number of rooms xiii e) Construction technology f) The number of floors The 30 projects selected for estimation were classified in accordance with these criteria and the number of the functional elements were analyzed so that the information concerning functional elements depending on the develeopment of the design phase. Within the second phase of the thesis are the effects of the finishings used to cover the functional elements on the quality classification and total cost of the buildings. For that purpose, alternative finishing materials have been developed at the quality to respond the needs of users and that would also be used for controlling the cost of the building. As these alternatives all have different unit costs, it has been possible to make a plan concerning total cost of the building. This model finds two ways of usage. Within the first method, the pre- design of the building is made. At that stage, the architect or the cost estimator measures the functional elements from the project and multiplies them by their unit prices, which leads to total cost when accumulated. After that, he will try to place the cost of the building within the required limits by trying other finishing options. This model might be used at the stage where no design is made. It would be possible to estimate and plan the cost by defining the building that is required to be designed. The data obtained by previous 30 projects that were analyzed before might be used. At that stage, design resolutions might occur as follows : a) The coverage of the construction site is determined b) The number of apartments per floor area determined c) The floor area is determined d) The number of rooms in the apartments are determined e) Or more than one criteria appearing herein might be determined XIV The aim of the above classification is to estimate the cost of the building preliminary design phase more accurately. An advantage of this model is the advantage of defining the appropriate building and construction quality class. Using such a method will provide the architect and the client to save time without dealing with the expensive alternatives but working out the best appropriate design alternative.
A Cost Estimating Model At Pre-design Stage - Based On Functional Elements
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1996
Keywords: Konut projeleri; Maliyet tahmini; Ön tasarım; Housing projects; Cost estimation; Preliminary design